On the Challenges to Documenting Requirements in Agile Software Development: A Practitioners’ Perspective - Canedo, Edna Dias; Calazans, Angelica Toffano S.; Silva, Geovana Ramos Sousa; Masson, Eloisa Toffano Seidel; Brito, Isabel Sofia (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2024)
Agile Software Development (ASD) is an iterative and incremental methodology designed to accelerate project deliveries. In this dynamic environment characterized by constant changes, the task of documenting requirements becomes increasingly challenging, leading to the emergence of the technical debt issue. This research involved a survey of 84 practitioners to identify the techniques and practices employed in documenting software requirements within ASD teams, as well as their perceptions of the documentation process and the challenges, regarding what factors influence it and its consequences. Our key findings indicate that user stories are the most commonly utilized technique by practitioners for documenting requirements. Furthermore, a deficient documentation process results in two primary consequences: rework and a knowledge deficit. To address these challenges, various techniques are implemented across different development phases, including requirement refactoring, documentation refinement meetings, and template reviews. Participants also emphasized the significance of having a requirements expert to enhance the documentation process and expressed uncertainty regarding the adequacy of their existing requirements documentation.